Comparative Analysis of Microwave Link Using Space and Hybrid Diversity Configuration on Mountain Topography Area - Ade Wahyudin; Alfin Hikmaturokhman (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2021)
The development of information and communication technology (ICT) in Indonesia is increasing rapidly every year. However, this increase is not comparable to the distribution of technology in remote areas, especially areas with mountainous contours. So it takes a proper backhaul network design to deploy telecommunication services in remote areas. Microwave transmission technology is widely used as a backhaul network in mountainous areas because it can reach areas that are difficult to reach by fiber optic. However, multipath fading becomes a problem in microwave communication, so to solve it, we use the diversity configuration approach. Space diversity configuration is the system most often used, but in more extreme conditions it can use a hybrid diversity configuration which is a combination of space and frequency diversity. In this study, we designed and compared the performance of two types of diversity configurations, namely space and hybrid diversity in cross-mountainous areas using simulation software Pathloss 5.0. Before comparison, these paths were tested with a point-to-point configuration to assess microwave communication performance without diversity. Based on the simulation, the resulting cross-mountain microwave communication performance using point-to-point configuration results in 99.98179% availability and 5742.79 seconds unavailability in one year, these values are still far from the ITU-T G.821 standard, namely 99.99% availability. In the configuration using Space Diversity, the quality has increased, but it cannot meet ITU standards because it is only capable of producing 99.98333% to 99.98943% availability or comparable to un-availability for 5255.53 to 3332.48 seconds/year. Meanwhile, the hybrid diversity configuration can produce a performance that meets ITU standards with an availability of 99.99122% or equivalent to un-availability for 2769.79 seconds per year.